Capsaicinoid nonivamide improves nonalcoholic fatty liver disease in rats fed a high-fat diet - Naruemon Wikan; Jiraporn Tocharus; Sivanan Sivasinprasasn; Aphisek Kongkaew; Waraluck Chaichompoo; Apichart Suksamrarn; Chainarong Tocharus (Elsevier, 2020)
Nonalcoholic fatty liver disease (NAFLD) is a chronic disease that causes morbidity associated with metabolic syndrome. NAFLD is a worldwide problem and represents a major cause of liver injury, which can lead to liver cell death. We investigated the effects of nonivamide (pelargonic acid vanillylamide, PAVA; 1 mg/kg) and rosuvastatin (RSV; 10 mg/kg) on hepatic steatosis induced by a high-fat diet (HFD). Male Sprague-Dawley rats were fed a HFD for 16 weeks then received PAVA or RSV for 4 additional weeks. We examined the metabolic parameters, function, fat content, histological alterations, reactive oxygen species production, and apoptotic cell death of the liver, in addition to the expression of the following important molecules: transient receptor potential cation channel subfamily V member 1 (TRPV1) phosphorylation of sterol regulatory element binding protein (pSREBP-1c/SREBP-1c), total and membrane glucose transporter 2 (GLUT2), 4-hydroxynonenal (4-HNE), and cleaved caspase-3. HFD-induced hepatic steatosis was associated with significantly increased morphological disorganization, injury markers, oxidative stress, lipid peroxidation, and apoptosis. However, metabolic dysfunction and hepatic injury were reduced by RSV and PAVA treatment. PAVA regulated lipid deposition, improved insulin resistance, and decreased oxidative stress and apoptotic cell death. Therefore, PAVA represents a promising therapeutic approach for treating metabolic disorders in patients with NAFLD.